Predictive value of a novel pragmatic tool for post‐stroke aspiration risk: The Functional Bedside Aspiration Screen. Issue 10 (26th July 2019) - Virvidaki, Ioanna‐Eleni; Giannopoulos, Sotirios; Nasios, Grigorios; Dimakopoulos, Georgios; Michou, Emilia; Milionis, Haralampos
Abstract: Background: There is still a strong need for an optimal clinician‐friendly screening tool for the identification of aspiration risk in stroke patients. In this study, we present the development of a novel, context‐specific screening tool for the prediction of aspiration risk on recent stroke survivors, the Functional Bedside Aspiration Screen (FBAS), and examine its construct validity, reliability with the predictive values toward pragmatic patients' outcomes. Methods: We conducted a prospective validation study of 104 acute ischemic stroke patients admitted to clinical wards in a tertiary university hospital. A group of experts developed and administered the FBAS 10‐point scale to all patients. Outcome measures were compared with those of the validated Yale Swallow Protocol (YSP, reference measure) and health indicators. Key Results: A strong association was found between the FBAS cutoff criterion and the YSP (Pearson χ 2  = 54.92, P  < .001). A score of ≤8 on the FBAS presented with 93.3% sensitivity and 83.3% specificity in deeming patient with reduced safety for oral nutrition (AUC = 0.934, CI = 0.884‐0.985). An inverse relationship was found between performance on the FBAS and in‐hospital and long‐term outcome indicators. Patients who failed the FBAS were 1.82 times more likely to develop aspiration pneumonia (95% CI = 1.42‐2.35) and 1.35 times more likely to develop pneumonia within 3 months postonset (95% CI = 1.15‐1.59). Conclusions and Inferences: The FBAS is a potentially useful tool for timely prediction of aspiration risk and health outcome in acute stroke. Abstract : The Functional Bedside Aspiration Screen (FBAS) is a potentially useful clinical support tool for prompt recognition of patients at risk for aspiration following an ischemic stroke. Lower performance on the FBAS is associated with higher risk of aspiration and general worse health outcome.